Macular degeneration: peculiar sunlight exposure in an agricultural worker - Oddone, Enrico; Taino, Giuseppe; Vita, Silvia; Schimd, Monica; Frigerio, Francesco; Imbriani, Marcello (La Medicina del Lavoro, 2019)
Background: Occupational exposure to sunlight, in particular to blue light (wavelength of 380-550 nm), is a risk factor for several pathologies, including chronic retinal photochemical damage and, more specifically, age-related macular degeneration (AMD). Moreover, in addition to the effect of blue light, there is evidence about the role of near ultraviolet light (UV-A) as a risk factor for AMD since, given the wavelength, a precise “turning point” between effect and no effect is not definable. Methods and results: This work reports the case of a woman employed in the agricultural sector from 15 to 25 years of age, with no significant occupational exposure to other risk factors for AMD, who later developed this pathology. The case is of particular interest given that she worked as a “mondina”, a task involving the transplanting of young rice seedlings into water-flooded fields and manual weed control. This practice, although replaced by the introduction of pesticides, entailed the exposure to sunlight reflection on the water surface in addition to direct exposure to natural light. Conclusion: This brief case-report points out that occupational exposure to the short wavelength component of visible light and UV-A deserve further attention regarding preventive measures and the adoption of adequate personal protective equipment, in particular in productive sectors involving lengthy eye exposure to solar radiation and to the reflectance of surrounding surfaces. Furthermore, the cases of AMD and cataract should receive a complete and accurate occupational anamnesis for a more proper recognition of the possible role of occupational solar radiation exposure in the induction of the disease.